Analysis of Implementation Safety and Health Occupational Management System in Kertosono General Hospital - Dian Hadi Purnomo; Indasah Indasah; Byba Melda (Journal for Quality in Public Health, 2018)
Kertosono Regional General Hospital has a high risk exposure and is the biggest hospital in Kertosono area, Nganjuk regency, so to prevent accidents and occupational diseases, it is necessary to manage K3 management through the implementation of the implementation of Occupational Safety and Health Management System (SMK3RS). This study aims to get a picture of the implementation or implementation of Occupational Safety and Health Management System (SMK3RS) implemented in RSUD Kertosono. The research design used was qualitative research with thematic analysis and by using observation method, in-depth interview, and documentation. Sampling technique used is purposive sampling with informant as many as ten people are structural hospital officials who have worked in RSUD Kertosono minimum five years and above. This research resulted that K3 Management System in RSUD Kertosono not yet the establishment of K3 Committee because not yet have K3 general expert, in terms of policy and commitment of K3 even though only in the form of oral speech, process of implementation of SMK3RS which have been run although not maximal, support factor and factor which inhibits, efforts are made to reduce barriers in the implementation process of SMK3RS, the impact of SMK3RS implementation, and the desired expectation in the implementation of SMK3RS in RSUD Kertosono. This study concludes that basically OSH program has been run well according to legislation, although K3 still not become work culture which will create the creation of Zero accident in work environment specially in hospital.